VECM Analysis on the Short-Term and Long-Term Relationship between Southeast Asian Military Spending and Indonesian Economic Growth - Muhamad Samingan; Risman, Helda; Murtiana, Sri; Suwito; Yanto, Sri (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2024)
This study examines the relationship between military spending in Southeast Asia and Indonesia’s economic growth from 1990 to 2023, addressing the impact of defense expenditures on regional economic dynamics. The primary aim is to analyze how military spending, influenced by geopolitical and modernization factors, interacts with Indonesia’s economic performance, and to identify the long-term and short-term effects of this relationship. To achieve this, the study utilizes the Vector Error Correction Model (VECM), employing data from SIPRI and the World Bank, and applying statistical techniques such as stationarity tests, cointegration analysis, Granger causality, and impulse response functions. The results reveal a significant long-term equilibrium relationship where Indonesia’s economic growth influences regional military spending, but not vice versa. Specifically, the analysis shows that while economic growth in Indonesia reduces ASEAN military expenditures over the long term, short-term dynamics highlight a notable impact of economic changes on defense budgets. Variance decomposition indicates that Indonesia’s economic growth increasingly drives variations in Southeast Asian military spending, with limited reciprocal effects. Based on these findings, the study recommends aligning military modernization with sustainable economic objectives through sound fiscal management, strategic technological investments, and strengthened regional cooperation. The research suggests that balancing national security concerns with economic development is crucial for optimal resource allocation. Future studies should further investigate how technological advancements and non-traditional security challenges influence the relationship between military spending and economic growth in the region.